The Study of the Characteristics of a Microwave Plasma Jet Operated with Ar at Atmospheric pressure - Ayat J. Mohamed; Mohammed K. Khalaf; Awatif sabir Jasim (Tikrit Journal of Pure Science, 2022)
In recent years, non-thermal atmospheric pressure plasma has attracted wide interest in industrial and biomedical fields due to its many advantages, such as its high efficiency, simple systems, easy operation, non-toxic residue, and low cost. In this project, non-thermal (cold) plasma generated using a voltage source with a precise frequency (microwave up to 2.4GHz) using argon gas. The electrical properties studied to describe the discharges of argon gas plasma jets at different flow rates (Flow= (1, 2, 3, 4) L/min) and with voltages (150 V). The produced plasma jet column will be analyzed using Optical Emission Spectrometry (OES) technology to determine plasma parameters such as electron temperature (Te), electron density (ne), plasma frequency (fp), Debye length (λD), and Debye (ND) number of the argon plasma jet. We use the Boltzmann plot to determine the electron temperature (Te) in the plasma, and the electron density (ne) is calculated by Stark broadening. The value of the electron temperature decreases from (0.991-1.273) eV and the electron density rises from (2.173-3.664) x1017 cm-3 with higher gas flow rates, also the Plasma plume length rises from (1.1-3.5) cm with higher gas flow rates, while the plasma jet temperature decreased with higher gas flow rates.